Mechanisms of Disinformation Amplification in Hybrid Warfare: The Case of the Conflict in Ukraine - Rafał ROMAŃSKI (Bulletin of "Carol I" National Defense University, 2025)
This article presents an interdisciplinary analysis of disinformation amplification mechanisms within the context of contemporary hybrid warfare, with particular emphasis on the armed conflict in Ukraine. The study aims to identify and characterize the complex processes that amplify false narratives, influencing both social perception and the informational environment. The main research question posed is: What disinformation amplification mechanisms are employed under conditions of hybrid warfare, and how do they affect the shaping of public awareness and conflict perception? The methodology combines qualitative content analysis, source triangulation, and network analysis of selected case studies, including manual analysis of hashtags and discussion groups. These include instances of denialism related to the Bucha massacre, heroic mythology (the “Ghost of Kyiv”), false flag operations (Zaporizhzhia Nuclear Power Plant), amplification on TikTok and Telegram, the functioning of botnets, and #IStandWithRussia campaigns. The findings indicate that disinformation is not a one-off communicative act but an iterative structure supported by three interrelated domains: propaganda communication, cognitive psychology, and algorithmic technologies. In conclusion, the research question is addressed, and five strategic action areas are proposed: media literacy education, cooperation with digital platforms, international coordination, support for independent media, and the development of cognitive resilience within society. The article contributes a novel theoretical framework in the form of a “hybrid tripartite model” (communication–perception–algorithms), which may serve as a useful analytical tool in future studies of disinformation in conflict situations.